The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2208/kaigan.72.i_1285
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reclamation Project on Mercury-Contaminated Sediment Transport from Minamata Bay into the Yatsushiro Sea

Abstract: Minamata Bay which suffered from a major disaster called "Minamata Disease" has already remediated from 1977 to 1990 by carried out highly mercury (Hg) contaminated sediment and reclaimed it in the bay area. Furthermore, many studies reported that the mercury has reached Yatsushiro Sea, the outer part of Minamata Bay. It can be assumed that the sediment transport still occurs from remaining Hg concentration even after the remediation project. In order to investigate it, we try to simulate the transport of sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The effects of coastal topographical changes on benthic community assembly through changes in hydrodynamic and physicochemical regimes have been shown in both the Oiartzun estuary (Borja et al, 2013) and Pearl River estuary (Yang et al, 2018). However, a simulation study in Minamata Bay showed that reclamation slowed bottom current velocity from 6 to 3 cm/s at ebb tide (Fathya et al, 2016), which could help facilitate retention of larvae input from other areas. Marine biological communities are sometimes maintained by self‐retention of larvae from the site rather than by dispersal from other regions (Cowen & Sponaugle, 2009; Giangrande et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of coastal topographical changes on benthic community assembly through changes in hydrodynamic and physicochemical regimes have been shown in both the Oiartzun estuary (Borja et al, 2013) and Pearl River estuary (Yang et al, 2018). However, a simulation study in Minamata Bay showed that reclamation slowed bottom current velocity from 6 to 3 cm/s at ebb tide (Fathya et al, 2016), which could help facilitate retention of larvae input from other areas. Marine biological communities are sometimes maintained by self‐retention of larvae from the site rather than by dispersal from other regions (Cowen & Sponaugle, 2009; Giangrande et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…3). In the horizontal direction, the variable grid established by Fathya et al 14) was utilized, where the grid accuracy of Minamata Bay, and its surrounding regions is up to 62.5 m, whereas the grid accuracy of places further from Minamata Bay is 125 m and 250 m, respectively. The vertical grid adopts the σ coordinate system and is composed of five layers, each having 20% of the total depth.…”
Section: Methodology (1) Sample Collection and Processingmentioning
confidence: 99%
“…The calculation domain in the model was defined to contain both the Yatsushiro Sea and the Ariake Sea. The horizontal grid is a variable grid established by Fathya et al 14) , and the grid precision is 62.5 m, 125 m, and 250 m, respectively. The vertical grid adopts the σ coordinate system and consists of five layers, each of which is 20% of the total depth.…”
Section: ) Establishment Of Numerical Modelmentioning
confidence: 99%